The role of genomic location and flanking 3′UTR in the generation of functional levels of variant surface glycoprotein in Trypanosoma brucei. Issue 4 (11th October 2017) - Ridewood, Sophie; Ooi, Cher‐Pheng; Hall, Belinda; Trenaman, Anna; Wand, Nadina Vasileva; Sioutas, Georgios; Scherwitzl, Iris; Rudenko, Gloria
Summary: Trypanosoma brucei faces relentless immune attack in the mammalian bloodstream, where it is protected by an essential coat of Variant Surface Glycoprotein (VSG) comprising ∼10% total protein. The active VSG gene is in a Pol I‐transcribed telomeric expression site (ES). We investigated factors mediating these extremely high levels of VSG expression by inserting ectopic VSG117 into VSG221 expressing T. brucei . Mutational analysis of the ectopic VSG 3′UTR demonstrated the essentiality of a conserved 16‐mer for mRNA stability. Expressing ectopic VSG117 from different genomic locations showed that functional VSG levels could be produced from a gene 60 kb upstream of its normal telomeric location. High, but very heterogeneous levels of VSG117 were obtained from the Pol I‐transcribed rDNA. Blocking VSG synthesis normally triggers a precise precytokinesis cell‐cycle checkpoint. VSG117 expression from the rDNA was not adequate for functional complementation, and the stalled cells arrested prior to cytokinesis. However, VSG levels were not consistently low enough to trigger a characteristic 'VSG synthesis block' cell‐cycle checkpoint, as some cells reinitiated S phase. This demonstrates the essentiality of a Pol I‐transcribed ES, as well as conserved VSG 3′UTR 16‐mer sequences for the generation of functional levels of VSG expression in bloodstream form T. brucei . Abstract : Trypanosoma brucei expresses extremely abundant Variant Surface Glycoprotein (VSG) (∼10% total). We investigated this high VSG expression, and identified conserved 3′UTR sequences essential for mRNA stability. Functional VSG levels were only produced from a Pol I‐transcribed VSG expression site, while expression from the Pol I‐transcribed rDNA was variable and did not functionally complement. This highlights the essentiality of both VSG genomic location and conserved 3′UTR sequences for viability of bloodstream form T. brucei .